Effects of hot air drying time on properties of biomass brick. (25th October 2016) - Lu, Zeguang; Ma, Chao; Zhao, Ziyue; Jia, Wanda; Wang, Meng
Highlights: Moisture content and drying density of biomass brick are decreasing with the increasing hot air drying time from 0 to 96 h. Compression strength is increasing with the increasing drying time and decreasing moisture content and drying density. Elastic recovery deformation rate in thickness is greater than ones in width and length. Abstract: Biomass brick is made from poplar wood and corn stalk fibers and calcium hydroxide, and dried in the hot air drying environment where it is 50 °C in temperature and 32.1% in relative humidity and 0.12 m/s in air velocity. Moisture content and drying density are decreasing with the increasing drying time from 0 to 96 h. Compression strength is increasing with the increasing drying time and decreasing moisture content and drying density. Drying shrinkage deformation rate in length is greater than ones in width and thickness, and it is greater than the permanent and elastic recovery deformation ones. Elastic recovery and permanent deformation rates in width and thickness are greater than drying shrinkage deformation rate. When the brick is dried for 96 h, it is 9.10% in moisture content, 1.04 g/cm 3 in drying density, 1.28 MPa in compression strength, 1.23 N m/kg in the ratio of strength and density.